2009
DOI: 10.2298/abs0904777m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spirodiclofen on the reproductive potential of two-spotted spider mite (Acari: Tetranychidae) ovipositing females

Abstract: A laboratory bioassay was conducted to evaluate the effects of spirodiclofen on the survival and reproduction of young and mated females of two-spotted spider mite (Tetranychus urticae Koch). The females were sprayed with a series of acaricide concentrations (96, 48, 24, 12, and 6 mg/l) 24-30 h after adult emergence, i.e., at the age most likely to exhibit dispersal behavior and close to their reproductive maximum. The proportions of T. urticae females that survived treatment without symptoms of poisoning were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…On the other hand, the chemical product Spirodiclofen presented one of the highest LC 50 , with 38.8637 ml/L (Table 1) and could develop resistance by the red mite. Montoya et al (2017) tested this chemical product on adult females of T. urticae and found that it has slow effectiveness, while Marcic et al (2009) point out that mortality is lower within the first 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the chemical product Spirodiclofen presented one of the highest LC 50 , with 38.8637 ml/L (Table 1) and could develop resistance by the red mite. Montoya et al (2017) tested this chemical product on adult females of T. urticae and found that it has slow effectiveness, while Marcic et al (2009) point out that mortality is lower within the first 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The sublethal effect is the name given to this response. It may be manifested as reductions in life span (Shen et al 2021), development rates (Bozhgani et al 2018), fertility (Marcic et al 2009), fecundity (Amaral et al 2019), and changes in behavior such as feeding (Holland et al 1994), and oviposition (Marcic et al 2007). Thus, insecticides alone or in a mixture with acaricides can exert subtle and overt effects that must be considered when examining their impact on the B. yothersi population.…”
Section: Introductionmentioning
confidence: 99%